ANALYSIS OF THE TIME TO HOSPITAL ADMISSION FOR STROKE PATIENT IN DR SARDJITO HOSPITAL FROM 2011-2013 - , MUHAMMAD NURAZAM BIN AZMAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Stroke is a cerebrovascular disease that occurs due to the obstruction of oxygen supply to the brain, causing brain tissue to die. This in turn resulted in various disabilities to the patients such as paralysis and cognitive impairment and can even lead to death. This high number of mortality and morbidity is partly due to the delayed time to hospital admission after the onset of stroke in this study, we hope to see the progress of time to admission of strokes patients in Dr. Sardjito Hospital from the year 2009-2013 in order to know if the time to admission has improved for stroke patients over the years as this will greatly affect the prognosis for the stroke patients. The data from this study can be used by the hospitals and healthcare office to know about the current rate of time of admission and for the improvement of healthcare for stroke patients in the future. Aim: To analyze the time to admission of stroke in Dr. Sardjito Hospital from 2011-2013. Methods: This is a non-experimental research